Systemic metastasis-targeted nanotherapeutic reinforces tumor surgical resection and chemotherapy - Minjun Xu (Nature Portfolio, 2021)
Failure of conventional clinical therapies such as tumor resection and chemotherapy are mainly due to the ineffective control of tumor metastasis. Here, the authors show that a systemic metastasis-targeted nanotherapeutic may offer a powerful adjunct therapy for suppressing tumor metastasis.